2014
DOI: 10.2147/idr.s66268
|View full text |Cite
|
Sign up to set email alerts
|

Genotypes and phenotypes of Shiga toxin-producing Escherichia coli (STEC) in Abeokuta, Southwestern Nigeria

Abstract: PurposeTo characterize the prevalence of hemolytic Shiga toxin-producing Escherichia coli (STEC) with a multidrug-resistant pattern in different age groups in Abeokuta, Nigeria.MethodsNonrepetitive E. coli isolates were collected from 202 subjects with or without evidence of diarrhea. Each isolate was biochemically identified and antimicrobial susceptibility testing was performed using the disk diffusion method. A sorbitol fermentation test of all the E. coli isolates was done and the minimum inhibitory concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…In the overall, 79.2% of the STEC isolated were non-O157 STEC serotypes while 20.8% were E. coli O157:H7 ( Table 3 ). This finding is a confirmation that consumers are more exposed to non-O157 STEC from food sources than E. coli O157:H7 STEC in Nigeria, as it is the trend in other part of the world (Grant et al, 2011;Johnson et al, 2006); yet the reports on the incidence of non-O157 STEC infection in Nigeria is far lower than that of E. coli O157:H7 (Olowe et al, 2014). The high prevalence of non-O157 STEC in the current study supported previous reports on high level of these pathogens in the animals from which the meat and meat products are sourced in the southwestern Nigeria (Adenipekun et al, 2015;Ajayi et al, 2011;Nsofor et al, 2013;Ojo et al, 2010).…”
Section: Serological Identification and Distribution Of Stec O157 And...supporting
confidence: 51%
“…In the overall, 79.2% of the STEC isolated were non-O157 STEC serotypes while 20.8% were E. coli O157:H7 ( Table 3 ). This finding is a confirmation that consumers are more exposed to non-O157 STEC from food sources than E. coli O157:H7 STEC in Nigeria, as it is the trend in other part of the world (Grant et al, 2011;Johnson et al, 2006); yet the reports on the incidence of non-O157 STEC infection in Nigeria is far lower than that of E. coli O157:H7 (Olowe et al, 2014). The high prevalence of non-O157 STEC in the current study supported previous reports on high level of these pathogens in the animals from which the meat and meat products are sourced in the southwestern Nigeria (Adenipekun et al, 2015;Ajayi et al, 2011;Nsofor et al, 2013;Ojo et al, 2010).…”
Section: Serological Identification and Distribution Of Stec O157 And...supporting
confidence: 51%
“…In our study there was also high level resistance observed against augumentin (amoxicillin/clavunalate) with 65% resistance. This high level resistance is indicative of the presence of extended spectrum beta lactamase (ESBL) among our isolates, even though ESBL testing was not conducted on the isolates; a resistance to both cephalosporin and augumentin shows the presence of ESBL enzyme [18][19][20]. Pseudomonas aeruginosa, resistance to blactam antibiotics and aminoglyco-sides has been reported to be associated with the production of enzymes, such as, carbenicillin hydrolyzing b-lactamases, extended-spectrum blactamases (ESBL), oxacillinases, metallo-blactamases(MBLs) ae well as aminoglycosidemodifying enzymes [10,11].…”
Section: Discussionmentioning
confidence: 99%